Structural Logic of Umah Kantur Gayo Construction Elements - Cut Nursaniah; Muhammad Zairi Fadillah; Masdar Djamaluddin (Universitas Sebelas Maret Surakarta, 2023)
Umah kantur in the Gayo highlands is located in the Bukit Barisan section which is crossed by the Sumatran fault line, making this area prone to earthquakes. These vernacular houses were designed by local people using natural materials found in their environment, forming a hazard-responsive system of wooden construction. However, the current generation tends to forget this knowledge from their ancestors, why this construction was used and what is the logic of the structure in the building. This qualitative research observes to identify the construction process of the elements and joint systems of the umah kantur in the Pegasing-Gayo area. The results of the study concluded that the home construction system contains sustainability to be applied to the current simple wooden house construction. The use of nails in the construction of walls, zinc material for roof, and cast concrete for bases, is still capable of producing a construction that is rigid elastic, lightweight, and able to reduce earthquake forces. Evidenced by the occurrence of uniform swaying movements of the legs, body and head construction during an earthquake, so that the house is still sturdy today.